Prevalence of infectious bovine keratoconjunctivitis (IBK) among dairy cattle in 'Ladang Angkat' Faculty of Veterinary Medicine, Universiti Putra Malaysia - Thinakaran, Deva Darshini (2015)
Dairy industry plays an important role in our nations‟ agriculture sector. The government has targeted to increase the level of local milk production to 120 million litres and self-sufficiency at 8% by year 2020. Infectious bovine keratoconjunctivitis (IBK) is one of the major diseases in ruminants that may cause losses in economy. This disease is caused by Moraxella bovis bacteria and governed by multifactorial factors such as vectors (flies, ticks and etc), environment and breed predisposition. impact is infectious bovine keratoconjunctivitis (IBK). There is limited information related to IBK disease among dairy cattle in Malaysia. Therefore this study was designed to determine the disease prevalence from dairy cattle in Program "ladang angkat‟ Faculty of Veterinary Medicine, UPM. Sub conjunctival swabs were collected from 50 dairy cattle and the samples were subjected for isolation and identification of the causative agent using polymerase chain reaction (PCR) technique. The result from this study indicates prevalence rate of IBK among dairy cattle in Program „ladang angkat‟ Faculty of Veterinary Medicine, UPM only 2%. There were no significant correlation between the disease and risk factors in these farms. In conclusion, IBK disease does not cause production loss in dairy farms of Program "Ladang Angkat‟, Faculty of Veterinary Medicine, UPM.